Stability and Development of the Banking System of the Republic of Armenia in the Post-Covid Period - Harutyunyan, Rafik (ՀՀ ԳԱԱ)
Risks associated with the financial stability of the banking system of Armenia arise mainly from three sources: the external economy, the domestic economy, and the financial system itself. The latter is usually considered separately since the financial system is a special component of the economy. In recent years, the banking sector of Armenia has been subject to some shocks and the accumulation of systemic risk, which has led to a higher level of dollarization and thereby limited the ability of the Central Bank to influence the economic environment through traditional monetary policy instruments. Риски, связанные с финансовой стабильностью банковской системы Армении, возникают в основном из трех источников: внешней экономики, внутренней экономики и самой финансовой системы. Последнее обычно рассматривают отдельно, поскольку финансовая система является особой составляющей экономики. В последние годы банковский сектор Армении подвергся ряду потрясений и накоплению системного риска, что привело к более высокому уровню долларизации и тем самым ограничило возможности Центрального банка влиять на экономическую среду с помощью традиционных инструментов денежно-кредитной политики. Հայաստանում բանկային համակարգի ֆինանսական կայունության տեսանկյունից ծագող ռիսկերն առաջանում են հիմնականում երեք աղբյուրներից` արտաքին տնտեսությունից, ներքին տնտեսությունից և բուն ֆինանսական համակարգից: Վերջինը սովորաբար դիտարկվում է առանձին, որովհետև ֆինանսական համակարգը տնտեսության առանձնահատուկ բաղադրատարրն է:
Keywords: Social and Humanitarian Sciences